Constructing a Collaborative Critique-Learning Environment for Exploring Science Through Improvisational Performance. (November 2019) - Wright, Christopher G.
This exploratory design experiment investigates Black male youth's participation in a science-learning environment designed to conceptualize the practice of critique as improvisational performance. The research highlights the young men's deployment of a linguistic practice, signifying, used to co-construct and enact the practice of collaborative critique. Implications include calling for the continued reimagining of teaching and learning science within urban contexts, including the need for educators to develop the required skills for recognizing and building upon students' potential resources. The theoretical and pedagogical choices incorporated in this study contrasts often-utilized discourses of deficiency associated with science education in urban contexts.